RE-INTERPRETATIONS AND EXTENSION OF THE THEORIES OF MORAL DEVELOPMENT - Daniela Jeder (Association of Social and Educational Innovation, 2020)
This paper aims at an analysis of some extensions and reinterpretations of the classical theories of moral development such as the theories of Carol Gilligan (moral / ethical worries), M. Swainson, Norman J. Bull etc. and, last but not least, a presentation of new directions of approach to morality - from the perspective of neuromoral and theories proposed by specialists such as Paul Jak and the renowned neurologist and biologist Robert Sapolsky. All this, in order to draw conclusions about how the theories of moral development can be capitalized in the educational space.